Blending Extensive and Intensive Reading to Enhance Critical Reading Skills in The EFL Context - Ilyas, Hamzah Puadi; Istaryatiningtias, Istaryatiningtias (JOLLT Journal of Languages and Language Teaching, 2025)
This study explores the integration of extensive and intensive reading strategies and their impact on critical reading and critical thinking skills in an English as a Foreign Language (EFL) context. The research addresses two primary questions: What challenges do EFL students encounter when engaging in extensive and intensive reading? and In what ways does the integration of these reading strategies influence students' critical reading skills? A qualitative research design was employed, involving 19 EFL students in the fourth semester of a private university in Jakarta. Specifically, the study applied a thematic analysis approach to systematically interpret the data, ensuring that emerging categories captured the complexity of students’ experiences. Data were collected through student reflections, interviews, and classroom observations during a 14-session reading course. Key findings reveal that students face challenges in text selection, vocabulary constraints, time management, and critical analysis. However, the integration of both reading strategies enhanced students' comprehension strategies, analytical thinking, and motivation. Students demonstrated greater confidence in discussions, improved inferencing abilities, and the ability to connect ideas across texts. The results highlight important pedagogical implications, suggesting that teachers should adopt a balanced integration of extensive and intensive reading to foster critical literacy, while policymakers and curriculum designers can draw on these insights to strengthen reading components in EFL programs. These findings suggest that integrating extensive and intensive reading approaches can significantly enhance EFL students' critical reading skills, providing valuable insights for future teaching practices. The study contributes to the theoretical understanding of reading instruction in EFL settings and offers practical recommendations for integrating these strategies in classroom settings.